2010
DOI: 10.1128/aem.01797-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technological Processes on the Tenacity and Inactivation of Norovirus Genogroup II in Experimentally Contaminated Foods

Abstract: Contaminated food is a significant vehicle for human norovirus transmission. The present study determined the effect of physicochemical treatments on the tenacity of infective human norovirus genogroup II in selected foods. Artificially contaminated produce was subjected to a number of processes used by the food industry for preservation and by the consumer for storage and preparation. Virus recovery was carried out by using ultrafiltration and was monitored by using bacteriophage MS2 as an internal process co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 85 publications
(111 reference statements)
1
44
0
Order By: Relevance
“…Available evidence suggests that NoV becomes internalized and disseminated in fresh produce (48,58,59). None of the decontamination methods investigated thus far has been shown to effectively inactivate NoV in fresh produce (18,20,22,40,45,52). In this study, we systematically investigated the survival of a human NoV surrogate (MNV-1) by HPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available evidence suggests that NoV becomes internalized and disseminated in fresh produce (48,58,59). None of the decontamination methods investigated thus far has been shown to effectively inactivate NoV in fresh produce (18,20,22,40,45,52). In this study, we systematically investigated the survival of a human NoV surrogate (MNV-1) by HPP.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, none of the decontamination methods inves-tigated thus far have been shown to effectively control human NoV in fresh produce (12,18,20,22,40,45,52). Sanitizers are not effective in the removal of food-borne viruses from fresh produce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The virus is transmitted primarily through the fecal-oral route, either by direct contact with fecal matter or indirect contact through contaminated food or water supplies. It is highly stable and contagious, requiring less than 10 virus particles to cause an infection (20,35,44,51). Recent human volunteer study and mathematical modeling showed that the average probability of infection for a single norovirus particle is close to 0.5 (56).…”
mentioning
confidence: 99%
“…Therefore, developing methods to evaluate the magnitude of inhibition is essential (14,42). Exogenously added control nucleic acids have been used for this purpose (14,27,30,32,37,42). Although the inhibition of polymerase activity depends on the target nucleotide sequences (22,40), most previous studies have not employed sequence-matched controls (27,30,32,37,42).…”
mentioning
confidence: 99%